Baltijos valstybių klausimas Vakarų valstybių politikoje 1944-1945 metais - Kraujelis, Ramojus (Lietuvos istorijos studijos, 2004)
The considerations of the three Great powers in the final years (1944-1945) of World War II and the question of the Baltic states within the context of international relations and diplomacy of these powers are discussed in the article.  In the last years of World War II, the United States were engaged in the creation of the new post-war international organizational model. Participation of the Soviet Union in these postwar plans was an essential condition. In that period of World War II, the question of Baltic states had no significant and independent role in the entire international balance of power. This opinion is grounded on the examples from diplomatic papers which confirm that Baltic states in inter-Allied relations were treated only as a bargaining agent.  Considering that in the Teheran conference (1943), Western states accorded the two of the Baltic states to Soviet interest sphere, the U.S. and Britain entered the Yalta conference (1945) with no illusions as to the fate of the Baltic States in particular and Eastern Europe in general.  The only one positive aspect regarding Baltic state survived - notwithstanding Soviet attempts, Western states remained firm in its legal commitment regarding Lithuania and the other Baltic States - to not recognize the forcible annexation of Baltic states. Accordingly, Western Allies did not recognize Lithuanians, Latvians, and Estonians as "Soviet citizens" within the context of the 1945 Repatriation Agreement.  In reality, the decisive effect of World War II was attempts to retain balance of power in international politics, but not moral or legal commitments. The end of World War II did not restore the independence of Lithuania and other Baltic states. The postwar international system that was leading to division of Europe, bipolar world, and Cold War was the adversity that influenced the plight of small states and nations.